Serum level of soluble interleukin‐2 receptor is positively correlated with metabolic tumor volume on 18F‐FDG PET/CT in newly diagnosed patients with diffuse large B‐cell lymphoma - Hajime Senjo; Minoru Kanaya; Koh Izumiyama; Koichiro Minauchi; Kenji Hirata; Akio Mori; Makoto Saito; Masanori Tanaka; Hiroaki Iijima; Eriko Tsukamoto; Kazuo Itoh; Shuichi Ota; et al. (Cancer Medicine)
Abstract Diffuse large B‐cell lymphoma (DLBCL) is the most frequent subtype of non‐Hodgkin lymphoma. High total metabolic tumor volume (TMTV) calculated using 18F‐FDG PET/CT images at diagnosis predicts poor prognosis of patients with DLBCL. However, high cost and poor access to the imaging facilities hamper wider use of 18F‐FDG PET/CT. In order to explore a surrogate marker for TMTV, we evaluated the correlation between the serum levels of soluble interleukin‐2 receptor (sIL‐2R) and TMTV in 64 patients with DLBCL, and the results were verified in an independent validation cohort of 86 patients. Serum levels of sIL‐2R were significantly correlated with TMTV. ROC analysis revealed that the cutoff value of TMTV ≥150 cm3 or sIL‐2R ≥ 1300 U/mL could predict failure to achieve EFS24 with areas under the curve (AUC) 0.706 and 0.758, respectively. Each of TMTV ≥150 cm3 and sIL‐2R ≥1300 U/mL was significantly associated with worse 5‐year overall survival and event‐free survival. Importantly, each of sIL‐2R <1300 U/mL or TMTV <150 cm3 identified patients with favorable prognosis among NCCN‐IPI high‐intermediate and high‐risk group. Serum level of sIL‐2R represents a convenient surrogate marker to estimate metabolic tumor burden measured by 18F‐FDG PET/CT that can predict treatment outcomes of patients with DLBCL.